Screening and Identification of Multi Compounds in Yitongshu Injection using Combination of Liquid Chromatography/Time-of-Flight Tandem Mass Spectrometry - Li, Fei; Cheng, Wei-Ming; Di, Xin; Zhao, Chun-Jie (Asian Journal of Chemistry, 2011)
An approach for screening and identification of multi components in complex traditional Chinese medicine systems using combination of liquid chromatography/time-of-flight tandem mass spectrometry technique was described in this paper. The chemical profile of Yitongshu injection, a well-known traditional Chinese formula in China, was studied using the established method as for an application. As a result, 22 components in Yitongshu injection were identified in this complex traditional Chinese medicine. The method was validated by imperatorin, ligustilide and osthol, three representative compounds in Yitongshu injection. The determination of three compounds was performed by an HPLC-UV method. The results indicated that the developed HPLC method is simple, sensitive and reliable for the determination of three representative compounds with a good linearity(r2 > 0.9995), precision(relative standard deviation (RSD) < 1.9) and the recovery range of 93.8-97.7 %. This study is expected to provide a rapid, sensitive, economical and systematical method for the identification and further quality evaluation of complex traditional Chinese medicines.